2015
DOI: 10.1186/s12951-015-0098-0
|View full text |Cite
|
Sign up to set email alerts
|

Design and characterization of a new peptide vector for short interfering RNA delivery

Abstract: RNA interference holds tremendous potential as one of the most powerful therapeutic strategies. However, the properties of short interfering RNA (siRNA), such as hydrophilicity, negative charge, and instability in serum have limited its applications; therefore, significant efforts have been undertaken to improve its cellular uptake. Cell penetrating peptides have been utilized to deliver various biologically active molecules, such as proteins, liposomes, nanoparticles, peptide nucleic acids, and recently small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
2
8
0
Order By: Relevance
“…These factors including positive surface charge and small particle size must have contributed to the increased transfection efficiency. Our results were supported by other studies indicating that the amount of positive charges on the cell surface and the size of the vector/oligonucleotide complex played important roles in determining successful gene delivery [4143]. A positively charged structure is desirable since it can preferentially adhere to the negatively charged cell surface receptors, leading to endocytosis.…”
Section: Discussionsupporting
confidence: 86%
“…These factors including positive surface charge and small particle size must have contributed to the increased transfection efficiency. Our results were supported by other studies indicating that the amount of positive charges on the cell surface and the size of the vector/oligonucleotide complex played important roles in determining successful gene delivery [4143]. A positively charged structure is desirable since it can preferentially adhere to the negatively charged cell surface receptors, leading to endocytosis.…”
Section: Discussionsupporting
confidence: 86%
“…Cell-penetrating peptides (CPPs) are short peptides (<30 amino acids), often cationic and have the ability to internalize into the eukaryotic cells without causing significant membrane damage ( 1 2 ). Owing to this intrinsic cell-penetrating property, CPPs are capable of delivering conjugated therapeutic molecules like proteins ( 3 ), peptides ( 4 ), nucleic acid ( 5 8 ), small molecule drugs ( 9 ), nanoparticles ( 10 11 ), etc. to the cells and tissues.…”
Section: Introductionmentioning
confidence: 99%
“…For example, CPP CADY with +5 charge and no fatty acid modification has estimated siRNA binding to CPP K D at 15 nmol/L concentrations in MQ 37, 38. Another study reported a K D  value of 224 nM in MQ measured by iTC for a peptide with charge 5.0–5.5 in water 25 . For a C6 peptide with seven arginines in its sequence, a K value of 9.23 × 10 6 M −1 was reported in water, resulting in a K D  value of ∼108 nM 26 .…”
Section: Discussionmentioning
confidence: 99%
“…This change of net charge affects the interactions between a CPP and the cargo. Isothermal calorimetry (iTC) is an accurate method that has been used to study mainly protein-ligand interactions, but a growing number of studies harness iTC to study CPP-ligand interactions, 24 CPP-siRNA interactions,25, 26 and CPP interactions with membranes 27 . Furthermore, iTC enables to determine the binding constant of a CPP to cargo and calculate values of apparent dissociation constants.…”
Section: Introductionmentioning
confidence: 99%